2012
DOI: 10.3389/fpsyg.2012.00313
|View full text |Cite
|
Sign up to set email alerts
|

From Risk-Seeking to Risk-Averse: The Development of Economic Risk Preference from Childhood to Adulthood

Abstract: Adolescence is often described as a period of heightened risk-taking. Adolescents are notorious for impulsivity, emotional volatility, and risky behaviors such as drinking and driving under the influence of alcohol. By contrast, we found that risk-taking declines linearly from childhood to adulthood when individuals make choices over monetary gambles. Further, with age we found increases in the sensitivity to economic risk, defined as the degree to which a preference for assured monetary gains over a risky pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…These processing and inhibition demands may explain some of the failures. Furthermore, children at this age seem to be particularly willing to choose risky high‐payoff options over more probable low‐payoff ones (Harbaugh, Krause, & Vesterlund, ; Paulsen, Platt, Huettel, & Brannon, ). Such a temptation to gamble may have led some children to choose the box containing the highest reward instead of the box their partner was most likely to choose.…”
Section: Discussionmentioning
confidence: 99%
“…These processing and inhibition demands may explain some of the failures. Furthermore, children at this age seem to be particularly willing to choose risky high‐payoff options over more probable low‐payoff ones (Harbaugh, Krause, & Vesterlund, ; Paulsen, Platt, Huettel, & Brannon, ). Such a temptation to gamble may have led some children to choose the box containing the highest reward instead of the box their partner was most likely to choose.…”
Section: Discussionmentioning
confidence: 99%
“…During adolescence, individuals may be more tolerant of the risk associated with offending or may even engage in the behavior precisely because it is risky. Paulsen, Platt, Huettel, and Brannon (2012) demonstrated a linear decline in tolerance for risk from adolescence to adulthood. Tymula, Glimcher, Levy, and Rosenberg Belmaker (2012) also found evidence that adolescents are more tolerant of risk when compared with adults, and they argued that this tolerance is responsible for the high rate of risky behaviors during adolescence (see also Burnett, Bault, Coricelli, & Blakemore, 2010).…”
Section: Age-graded Marginal Utilities Of Subjective Expectationsmentioning
confidence: 99%
“…It may be, however, that limited inhibitory control capacities could have masked coordination abilities in some children, resulting in fairly low conformity rates even when coordination was necessary. Moreover, previous studies have shown that children at this age seem to be particularly willing to choose risky high‐pay‐off options over more probable low‐pay‐off ones (Harbaugh, Krause, & Vesterlund, ; Paulsen, Platt, Huettel, & Brannon, ). Such a temptation to gamble may have led some children to choose the box containing the highest reward instead of the box their partner was more likely to have chosen.…”
Section: Discussionmentioning
confidence: 96%